Evolution of late steps in exocytosis: conservation and specialization of the exocyst complex - Boehm, Cordula; Field, Mark C (Wellcome open research, 2019)
Background: The eukaryotic endomembrane system most likely arose via paralogous expansions of genes encoding proteins that specify organelle identity, coat complexes and govern fusion specificity. While the majority of these gene families were established by the time of the last eukaryotic common ancestor (LECA), subsequent evolutionary events has moulded these systems, likely reflecting adaptations retained for increased fitness. As well as sequence evolution, these adaptations include loss of otherwise canonical components, the emergence of lineage-specific proteins and paralog expansion. The exocyst complex is involved in late exocytosis and additional trafficking pathways and a member of the complexes associated with tethering containing helical rods (CATCHR) tethering complex family. CATCHR includes the conserved oligomeric Golgi (COG) complex, homotypic fusion and vacuole protein sorting (HOPS)/class C core vacuole/endosome tethering (CORVET) complexes and several others. The exocyst is integrated into a complex GTPase signalling network in animals, fungi and other lineages. Prompted by discovery of Exo99, a non-canonical subunit in the excavate protist Trypanosoma brucei, and availability of significantly increased genome sequence data, we re-examined evolution of the exocyst. Methods: We examined the evolution of exocyst components by comparative genomics, phylogenetics and structure prediction. Results: The exocyst composition is highly conserved, but with substantial losses of subunits in the Apicomplexa and expansions in Streptophyta plants, Metazoa and land plants, where for the latter, massive paralog expansion of Exo70 represents an extreme and unique example. Significantly, few taxa retain a partial complex, suggesting that, in general, all subunits are probably required for functionality. Further, the ninth exocyst subunit, Exo99, is specific to the Euglenozoa with a distinct architecture compared to the other subunits and which possibly represents a coat system. Conclusions: These data reveal a remarkable degree of evolutionary flexibility within the exocyst complex, suggesting significant diversity in exocytosis mechanisms.
Keywords: Exocytosis; exocyst; comparative genomics; membrane transport; eukaryotes; molecular evolution